#TITLE_ALTERNATIVE# - (NIM 25090003), HARIMURTI
Study in this thesis is for knowing the behaviour of shear strenght soft clay that is tested by Triaxial device. This soft clay is made by compacting soil slurry which have water contents 1.3 times liquid limit of natural soil. Shear strenght is tested by using CKoU method in order to achieve the same with field condition. CKou method is the way, where as long as the consolidation is not pleasured the deformation to lateral happened, whereas, when the shear time of it occured the lateral deformation, but is not pleasure there is the drainage. The examination is done after primer consolidation of soil which compacted have finished. First stage is done directly after the weight is up and tested by a mentioned ways, second stage after 12 days, third stage after 24 days, and forth stage after have 40 days old. The tested clay is divided by two, that are overconsolidated and normally consolidated. The result of the testing by CKoU method on the time indicate the increasing toward shear strength of it. Besides that, stress deviator, cohesion, total stress ratio, and efektive stress ratio indicate the increasing on time examination, while the indication decreasing is pore water pressure and parameter pore water.